Redescription of Rhyacophila yukii Tsuda 1942 and description of three new Rhyacophila species from Japan (Trichoptera: Rhyacophilidae) - Torii, Takaaki; Kobayashi, Tohru (Zootaxa, 2021)
Three new species of Rhyacophila (Trichoptera: Rhyacophilidae) from Japan are described. Among them, R. hattorii n. sp. and R. kobayashii n. sp. are assigned to the Rhyacophila sibirica Group. Another new species, R. kuranishii n. sp. is assigned to the Rhyacophila anatina Group. The figures of “R. yukii” by Schmid (1970) are actually of R. hattorii, not R. yukii Tsuda 1942. We describe these three new species, redescribe R. yukii, and discuss the diversity of this genus.